2005
DOI: 10.1186/1471-2210-5-2
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin, a citrus bioflavonoid, decreases the oxidative stress produced by carbon tetrachloride in rat liver and kidney

Abstract: BackgroundCCl4 is a well-established hepatotoxin inducing liver injury by producing free radicals. Exposure to CCl4 also induces acute and chronic renal injuries. The present study was designed to establish the protective effect of hesperidin (HDN), a citrus bioflavonoid, on CCl4-induced oxidative stress and resultant dysfunction of rat liver and kidney.MethodsAnimals were pretreated with HDN (100 and 200 mg/kg orally) for one week and then challenged with CCl4 (2 ml/kg/s.c.) in olive oil. Rats were sacrificed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
51
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(67 citation statements)
references
References 35 publications
8
51
0
1
Order By: Relevance
“…According to the literature data, radicals formed through metabolic conversion of CCl 4 , initiate the peroxidation of membrane poly-unsaturated fatty acids (PUFA) [11] [30] [33] with ultimate production of MDA and 4-HNE [3] [33]. These aldehydes are believed to be the main indicator of age pigment formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the literature data, radicals formed through metabolic conversion of CCl 4 , initiate the peroxidation of membrane poly-unsaturated fatty acids (PUFA) [11] [30] [33] with ultimate production of MDA and 4-HNE [3] [33]. These aldehydes are believed to be the main indicator of age pigment formation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that CCl 4 produces free radicals with consequent harmful damage to tissues such as the liver, kidneys, heart, lung and brain as well as blood [11]. One mechanism behind these damaging effects is the formation of trichloromethyl ( 3 CCl  ) and trichloromethylperoxyl ( 3 2 CCl O  ) radicals and the covalent binding of 3 CCl  to vital target molecules such as DNA, lipids, proteins and carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The belief causes of carbon tetrachloride are provoked hepatic destruction in lipid peroxidation and decline action of antioxidant enzymes and accumulation of free radicals. 6,7 Urtica dioica L. herbaceous plant that grows over a wide area of the world belongs to the family Urticaceae and includes more than sixty genera and about more than seven hundred species the commonly known as Stinging Nettle. 8,9 The diskette leaves rich in fine hair, which irritates the skin on contact because they contain many materials including acetylcholine, histamine.…”
Section: Introductionmentioning
confidence: 99%